2020
DOI: 10.1007/s10657-020-09671-5
|View full text |Cite
|
Sign up to set email alerts
|

Grounding the case for a European approach to the regulation of automated driving: the technology-selection effect of liability rules

Abstract: In the current paper, we discuss the need for regulation at EU level of Connected and Automated Driving solutions (henceforth CAD) based on multiple considerations, namely (i) the need for uniformity of criteria across European Member States, and (ii) the impact that regulation—or the absence of it—has on the proliferation of specific technological solutions. The analysis is grounded on legal and economic considerations of possible interactions between vehicles with different levels of automation, and shows ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…Robotów nie odstraszają groźby odpowiedzialności prawnej lub finansowej, ponieważ ich wolność osobista i bogactwo nie są zagrożone. Chcąc poradzić sobie z tym niedociągnięciem, naukowcy i decydenci analizują możliwość uczynienia robotów posiadaczami praw, obowiązków oraz aktywów, wzorując się na obecnym statusie korporacji (Bertolini, 2020;Bertolini, Riccaboni, 2020).…”
Section: Ponowne Przemyślenie śRodków Prawnych Dotyczących Deliktów R...unclassified
See 1 more Smart Citation
“…Robotów nie odstraszają groźby odpowiedzialności prawnej lub finansowej, ponieważ ich wolność osobista i bogactwo nie są zagrożone. Chcąc poradzić sobie z tym niedociągnięciem, naukowcy i decydenci analizują możliwość uczynienia robotów posiadaczami praw, obowiązków oraz aktywów, wzorując się na obecnym statusie korporacji (Bertolini, 2020;Bertolini, Riccaboni, 2020).…”
Section: Ponowne Przemyślenie śRodków Prawnych Dotyczących Deliktów R...unclassified
“…Należy stwierdzić, że nie istnieje ogólne sformułowanie odpowiedzialności za wypadki spowodowane przez roboty/sztuczną inteligencję, chociaż niektóre organy ustawodawcze próbowały przewidzieć niektóre problemy, mogące wyniknąć z deliktów robotów 4 . W dalszej części artykułu przedstawiono przykłady spektakularnych wdrożeń, aby zaobserwować, czy i jak prawo zareagowało na obecność aktorów--robotów w różnych obszarach społecznej i gospodarczej działalności.…”
Section: Aktualny Stan Prawny Robotówunclassified
“…These permissions are subject to certain requirements, including mandates that the vehicle be able to independently cope with driving responsibilities and comply with traffic laws, as well as to place itself into a lower-risk fail safe condition if necessary. The car owner must carry adequate insurance to cover the vehicle and the person who is using its autonomous functions, and the vehicles themselves must maintain information about its operation, which is to be made available to the government under certain circumstances [155]. The UNECE is also developing common, high-level principles toward autonomous vehicles (such as requiring validation, object detection, fail-safe criteria, etc.…”
Section: European Regulatory Counterpointmentioning
confidence: 99%
“…We have shown that, to date, there exists no general formulation of liability in case of robot accidents, and the proposed solutions differ across jurisdictions. The still open question concerns how legal incentives – so carefully calibrated to induce human actors to exercise precautionary care – need to be reshaped in robot accidents (Bertolini, 2013, 2020; Bertolini and Riccaboni, 2020; Casey and Lemley, 2019; De Chiara et al ., 2021; Epstein, 2021; Kovač, 2020; Lemley and Casey, 2019; Shavell, 2020; Talley, 2019).…”
Section: Introductionmentioning
confidence: 99%